Survival Strategies For Rice Farmers On Roductivity In Tanjung Beringin Village West Tabir Subdistrict - Nahdiati; Felia Siska; Yenni Melia; Mustaqim Mustaqim; Irwan, Irwan (CV Putra Publisher, 2025)
This research was motivated by the existence of an imbalance in rice productivity in Tanjung Beringin Village for the last five years from 2018-2022, where in 2022, there was a relatively low decline in rice productivity from the previous year. This problem shows that there are major challenges faced by rice farmers in Tanjung Beringin Village in terms of climate change, resource availability, and agricultural practices that have been carried out, so that rice farmers in Tanjung Beringin Village apply survival strategies so that rice productivity increases. Thus this study aims to analyze the survival strategy for rice farmers in productivity in Tanjung Beringin Village, West Tabir District. The theory used is the theory of survival strategies from Hardestry (1977). This research uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The data analysis used the interactive method of Miles and Huberman. The results of this study indicate that the strategy of rice farmers in Tanjung Beringin Village in maintaining productivity implements strategies: 1) Technology adaptation with the use of superior rice varieties and water management technology in the form of making small ponds or intermittent irrigation. 2) Socio-economic capacity building through strengthening cooperation between farmers, diversification of farming businesses, and utilization of local labor, 3) Environmental risk management strategies by using organic fertilizers, and conservative soil management.